Otolaryngological procedures during the COVID-19 pandemic - Lichota, Piotr; Wilczyński, Jacek; Zieliński, Rafał (Medical Studies/Studia Medyczne, 2021)
The purpose of this paper was to present a review of the scientific literature on carrying out typical otolaryngological procedures during the COVID-19 pandemic and periods of increased numbers of SARS-CoV-2 infections. The recommendations on reducing the risk of SARS-CoV-2 infection of ENT (ear, nose, and throat) professionals during typical otolaryngology procedures published by numerous authors are of great importance. The presented recommendations limit the use of unverified advice from the media, in particular, those published on the Internet by the otolaryngological environment not only during the first wave of increase in incidence but also during anticipated recurrent periods of increased numbers of infections caused also by mutated SARS-CoV-2.